The Effectiveness of Somatic, Auditory, Visual, Intellectual (SAVI) Method in Teaching Reading on Descriptive Text for Senior High School Students - Dessy Ayu Ardini; Ratna Nurlia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
To find the effect of Somatic, Auditory, Visual, Intellectual (SAVI) method on the students’ reading achievement was the aim of this study. Quasi experimental using non randomized pre-test posttest had been the research design in this study which involving first year students of senior high school as the subject of study. Class X5 was experimental group and class X7 was control group. To collect the data, pretest was given before the treatment. Somatic, Auditory, Visual, Intellectual (SAVI) method was given to experimental group and grammar translation method was given to control group. As result, T-score got from posttest with equal variance assumed was 6.604 with the probability 0.000 which was smaller than 0.05. It means the students taught by using Somatic, Auditory, Visual, Intellectual (SAVI) method achieved reading skill better than those who are taught by using Grammar Translation Method.